Vagino-cutaneous fistula: complication at 13 years after transobturator tape procedure - Aslan, M.; Yavuzkir, S.; Aslan, Ahmet (Springer London Ltd, 2021)
[Abstract Not Available]
Keywords: Mesh exposure; Mid-urethral sling surgery; Vagino-cutaneous fistula